Double Stage Shrinkage Estimation of the Reliability Function of the Proportional Hazard Family of Distribution Function under Different Loss Functions Using Progressive Type II Censored Sample (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we propose two double stage shrinkage estimators of the reliability function of the proportional hazard family of distribution functions, using progressive type II censored sample. The risk functions and relative risk functions of the suggested estimators are derived under symmetric and asymmetric loss functions, viz., the squared error loss function and the general entropy loss function. The results show that the proposed estimators have better performance than a classical estimator in terms relative risk.